Answer:
ab - a - b + 1 = (a - 1)(b - 1)
Explanation:
Let us explain factorization by grouping
In the expression of 4 terms ax + by + bx + ay
Take every two terms have a common factor in a bracket
Take the common factor out of the brackets
Take the bracket as a common factor
Let us do these steps with our question
∵ ab - a - b + 1 is an expression of 4 terms
→ Take ab and a in a bracket, -b and 1 in another bracket
∴ ab - a - b + 1 = (ab - a) + (-b + 1)
→ Take a as a common factor from the 1st bracket and -1 from
the 2nd bracket
∴ (ab - a) + (-b + 1) = a(b -1) + -1(b - 1)
→ Take the bracket (b - 1) as a common factor
∴ a(b -1) + -1(b - 1) = (b - 1)(a + -1)
∵ (+)(-) = (-)
∴ (b - 1)(a + -1) = (b - 1)(a -1)
→ Change the order of the bracket
∴ (b - 1)(a -1) = (a - 1)(b - 1)
∴ ab - a - b + 1 = (a - 1)(b - 1)